Between a Rock and a Hard Place: The Educational Dilemma of Migrant Children in China - Chuanyan Wang; Lu Xu (SAGE Open)
This article explores the educational challenges faced by migrant children in China, examining their experiences in both inflow cities and hometowns. Drawing on 94 in-depth interviews conducted in 2022 with returned migrant children and adults, as well as an empirical survey involving 1,865 returned migrant children and 344 teachers across 8 county-level cities in 4 provinces in 2023, the study reveals significant findings. Migrant children in China exhibit distinct characteristics: they typically arrive in inflow cities during preschool years and return to their hometowns during the transition from primary to middle school. They face dual adaptation challenges as they move from rural to urban schools and back again. These children often experience systemic exclusion in inflow cities and have to return to their hometowns to pursue post-compulsory education. However, they encounter substantial academic adaptation difficulties upon returning, and the most notable of these challenges are academic setbacks, with many teachers expressing pessimism regarding their chances of gaining admission to high school. The plight of migrant children highlights their “double dis-embedded” status within China’s mobility policies, where educational re-migration exacerbates rather than alleviates structural inequalities.